Heterochromatin patterns in triatomines of the genus Panstrongylus - Tartarotti, Ester [UNESP]; De Azeredo-Oliveira, Maria Tercília Vilela [UNESP] (My University, 1999)
Spermatogenesis was analysed by C-banding in two species of triatomines, Panstrongylus megistus and P. herreri. Both species revealed interstitial and terminal bands in the autosomes, which is a common pattern in Heteroptera. The terminal bands corroborated the hypothesis that in holocentric chromosomes the heterochromatin is preferentially located at the telomere. The sex chromosomes in P. herreri were totally heterochromatic in spermatogenesis, and in P. megistus the X chromosomes alternated between positive and negative banding.
Keywords: C-banding; Chagas' diseasé; Holocentric chromosomes; Panstrongylus spp; Spermatogenesis; Triatomines